PRESERVING JUDGEMENT OF TOPENG PANJI CIREBON FROM INDONESIAN TO ENGLISH: AN APPRAISAL ANALYSIS OF TRANSLATION TECHNIQUE - Fedro Iswandi; Amal Hayati; Khadeja (PT. Jurnal Center Indonesia Publisher, 2026)
This study investigates translation techniques used in rendering judgment evaluation from Indonesian into English at Topeng Gegesik book. The research focuses on the characterization of Topeng Panji Cirebon. The study applies (Molina & Albir, 2012) translation techniques framework to identify how judgment meanings are transferred into English. Using a qualitative descriptive method, the data consist of clauses containing judgment expressions in Indonesian and its translation in English. The findings reveal that translation techniques such as modulation, amplification, established equivalence and literal translation are predominantly employed to preserve positive judgment values especially normality and propriety. The study demonstrates that translation technique choices significantly influence the maintenance of cultural values, moral evaluation, and character identity. This research contributes to translation studies by integrating appraisal theory with translation techniques in the context of traditional cultural texts.